Corrective and preventive actions for damage product problem on raw materials for the pharmaceutical industry - Ajeng Sekarkirana Pramesti Kameswara; Denie Amanda Octavia; Rr. Nurul Rahmanita; Nico Resando Nainggolan; Muhammad Fajar Nur Iman; Erfa Fatoni Dwi Putra (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
One issue that plagues every industry is defective products, which is an unintended product quality deviation during the production process. In a pharmaceutical business situated in East Jakarta, Indonesia's Raya Bogor Street, data shows that when products were received from vendors, almost 30% of imported raw materials for Pharma X were damaged or defective. We apply the root cause analysis (RCA) method on faulty or damaged items to identify the fundamental issues that arise, and we offer solutions for preventive and corrective activities. As a result, the supplier is to blame for any damage to the bulk drum container. The answer and course of action that must be followed is to make sure that fiber drum deliveries from suppliers are more protected and that there are no longer any air shipments from the vendor's warehouse to the material warehouse